The value of hedging through corporate governance : a literature review and directions for future research - Jorge, Maria João (2015)
Previous empirical studies concerning corporate hedging have investigated several arguments that have been suggested to explain why corporate hedging is value-enhancing. Another stream of research examined the direct impact of hedging on firm value. Also in line with this, recent studies show that the corporate governance environment could be an important factor in understanding the value of hedging activities. This paper aims to present a comprehensive overview of the theoretical and empirical literature on these issues. We draw three main conclusions. First, it is necessary to identify appropriate measures of hedging activity beyond the use of derivatives. Second, it is essential to get more evidence on the effect of corporate governance in the value of hedging, not disregarding the possibility that these decisions can be undertaken simultaneously. Finally, it is important to expand empirical evidence to non-US firms.